Enhanced hydrogen evolution reaction performance of anatase-rutile TiO2 heterojunction via charge transfer from rutile to anatase - Arzaee N.A.; Yodsin N.; Ullah H.; Sultana S.; Mohamad Noh M.F.; Mahmood Zuhdi A.W.; Mohd Yusoff A.R.B.; Jungsuttiwong S.; Mat Teridi M.A. (Royal Society of Chemistry, 2024)
In light of recent doubts surrounding the industrial viability of photo(electro)catalysis technology for sustainable hydrogen production, it becomes imperative to align materials development with rationalized synthesis protocols. In this study, we present an innovative technique utilizing atmospheric-pressure chemical vapor deposition (APCVD) to rapidly produce TiO2 in just 5 minutes using pure TiCl4 as the sole reagent. The resulting photoanode exhibits exceptional photoelectrochemical (PEC) water-splitting performance, achieving a photocurrent density of 2.06 mA cm?2 at 1.23 V RHE. Moreover, the photoanode demonstrates sustained operation for 16 hours, leading to the successful collection of 138 ?mol of H2 and 62 ?mol of O2. These remarkable results are attributed to the controlled formation of an anatase-rutile phase-junction, the presence of well-balanced oxygen vacancies, and the bifrustum nanoparticle-nanoflake structure with a unique light trapping effect and large surface area. Density functional theory calculations confirm that the water-splitting reaction primarily occurs at undercoordinated Ti and O atoms in both anatase and rutile TiO2. Notably, the calculated Gibbs free energy values for the hydrogen evolution reaction (HER) differ significantly between rutile (?0.86 eV) and anatase TiO2 (0.22 eV). In the heterojunction, charge transfer enhances the HER performance through shared electronic density, resulting in a synergistic effect that surpasses the capabilities of individual surfaces and underscores the importance of electronic interactions within the junction. 2023 The Royal Society of Chemistry.